2017
DOI: 10.1088/1361-6528/aa536a
|View full text |Cite
|
Sign up to set email alerts
|

A model electrode of well-defined geometry prepared by direct laser-induced decoration of nanoporous templates with Au–Ag@C nanoparticles

Abstract: We present an original type of model electrode system consisting of bimetallic Au-Ag nanoparticles embedded in an amorphous carbon matrix with an extremely well-defined geometry of parallel, straight, cylindrical macropores. The samples are prepared in one step by direct laser deposition of the metal/carbon composite onto the inner walls of a porous 'anodic' alumina matrix serving as a template. The coating is homogeneous from top to bottom of the pores, and the amount of material deposited can be tuned by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It allows 'on-site' functionalization of various types of surfaces with NPs active in catalysis and electrocatalysis, surface-enhanced Raman spectroscopy (SERS), plasmon-enhanced fluorescence, energy conversion, solar cell technologies, etc. [17,18,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It allows 'on-site' functionalization of various types of surfaces with NPs active in catalysis and electrocatalysis, surface-enhanced Raman spectroscopy (SERS), plasmon-enhanced fluorescence, energy conversion, solar cell technologies, etc. [17,18,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies on the one-step laser-induced deposition method of AuAg/C composite, the choice of organometallic precursor, solvent, irradiation wavelength, and time crucially affect the quantity and quality of the coating [31,33,40]. For Ru/C deposition, we chose triruthenium dodecacarbonyl, Ru 3 (CO) 12 , as a 1 mg/mL 1,2-dichloroethane solution irradiated within its absorption band at 325 nm [4142].…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we address this goal with the synthesis of metal/carbon composites via the laser-induced deposition method already described for carbon-encapsulated Ag/Au nanoparticles (AgAu/C) [3133]. This practically appealing one-step technique bases on the photo-induced decomposition of a dissolved organometallic complex and the subsequent self-organization into hybrid metal/carbon nanostructures with controlled composition and morphology [32].…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on the photochemical decomposition of the metal-containing precursor under laser irradiation, followed by reduction of the metal and the formation of NPs [ 31 ]. As possible precursors, an extensive list of laboratory-synthesized and commercially available compounds were successfully demonstrated, such as organometallic complexes, inorganic, and organic salts [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. It was found that LID allows the user to control the coating density, morphology, and composition of the MNPs deposited on the substrate’s surface.…”
Section: Introductionmentioning
confidence: 99%